2005
DOI: 10.1590/s0006-87052005000400009
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e desenvolvimento da planta daninha capim-camalote

Abstract: (2) ; MURILO SALA MOREIRA (3) ; MARCELO NICOLAI (2) ; RAMIRO FERNANDO LÓPEZ OVEJERO (2) ; PEDRO JACOB CHRISTOFFOLETI (4) ; DANIEL MEDEIROS (5) RESUMOO capim-camalote (Rottboelia exaltata L.f.) é uma planta daninha com rápida disseminação nas áreas canavieiras do Brasil, causando significativas perdas de produtividade na cultura. Assim, esta pesquisa teve por objetivo avaliar o crescimento, o desenvolvimento vegetativo e a capacidade reprodutiva do capim-camalote, como mecanismo de melhoria do manejo a ser a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 10 publications
1
13
0
11
Order By: Relevance
“…The rapid development of Rottboelia spp. plants, such as in root and shoot formation, is due to its ability to accumulate phytomass, thus favoring its domination in space, because of the higher rate of absorption of water and nutrients, making them competitive against agricultural crops (Carvalho et al, 2005). The lowest heights of Rottboelia spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rapid development of Rottboelia spp. plants, such as in root and shoot formation, is due to its ability to accumulate phytomass, thus favoring its domination in space, because of the higher rate of absorption of water and nutrients, making them competitive against agricultural crops (Carvalho et al, 2005). The lowest heights of Rottboelia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Phenological stage was determined with the BBCH scale, where grades were assigned based on numbers ranging from 0 to 9, according to Hess et al (1997) (Table 1); the plants were subsequently identified when the phenological stage reached 50% + 1 of plants with a given growth feature (Carvalho et al, 2005). Ripening of fruit and seed 9…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparando-se as espécies de Amaranthus com outras espécies de plantas daninhas pode-se notar que o florescimento dos carurus foi semelhante à Rottboelia exaltata e à Murdannia nudiflora, que ocorreram aos 49 DAS e 54 DAS, respectivamente (ERASMO et al, 2003;CARVALHO et al, 2005a); e precoce em relação a Siegesbeckia orientalis e Chloris polydactyla, que ocorreram, cerca de 60 e 112 DAS, respectivamente (AGUILERA et al, 2004;CARVALHO et al, 2005b).…”
Section: Introductionunclassified